Perilaku Menyontek Ditinjau dari Locus of Control pada Pelajar SMA - Desi Desi; Rianda Elvinawanty; Winida Marpaung (Faculty of Psychology, Universitas Semarang, 2018)
Subject of the survey consist of 117 students on Sriwijaya senior high school by total sampling method. The results showed there were significantly relationship locus of contol with cheating. External with correlate coefficient 0.848 and sig. 0.000 (p<0.005), were positively related to cheating, while internal were negatively related to cheating with correlate coefficient -0.286 and sig. 0.000 (p<0.05). Calculations were performed to test the requirements analysis, which consists of normality distribution, multicollinearity, autocorrelation, and heteroscedasticity test for relationships. Data were analyzed by using multiple analysis regression. The results of data analysis showed a correlation correlation coefficient of 0.952 (p <0.05) and showed that the contribution of a given locus of control on cheating was 95.2 percent, while the remaining 4.8 percent was affected by other factors not examined. From the results, it can be concluded that the hypothesis stating that there is a significance relationship between locus of control and cheating.